Investigation of groundwater potential using gravity data in Wadi Fatimah and its surroundings, Western Saudi Arabia - Alshehri, Fahad; Mohamed, Ahmed (Frontiers in Earth Science, 2023)
Water scarcity is becoming a growing problem in the Middle East due to urbanization, industrialization, and population growth. Saudi Arabia is one of the region's largest consumers of water, so it is important to take immediate action to address this issue. This study used data from the Gravity Recovery and Climate Experiment (GRACE) to assess changes in groundwater storage in Wadi Fatimah and its surrounding areas. The results showed that the average annual rainfall (AAR) in Wadi Fatimah was 131 mm, while the AAR for the entire Makah province was 99.3 mm. The AAR in Makah province can be divided into three climatic periods: Period I (April 2002-December 2011): AAR of 92.8 mm; Period II (January 2012-December 2016): AAR of 101.8 mm and Period III (January 2017-December 2021): AAR of 116.4 mm. The GRACE-derived ΔTWS (time-variable gravity) variations were -0.18±0.023 cm/yr in Wadi Fatimah and -0.38±0.018 cm/yr in the entire Makah Province. The soil moisture storage (ΔSMS) varia-tions were +0.039±0.025 mm/yr in Wadi Fatimah and -0.008±0.002 mm/yr in the entire Makah Province. The average groundwater storage (ΔGWS) variation in Wadi Fatimah was -0.18±0.022 cm/yr, which indicates a slight decrease. The ΔGWS variation in the entire Makah region was -0.38±0.017 cm/yr, which indicates a negative trend. The study also found that surface runoff from rain-fall in the eastern section of Wadi Fatimah flows westward to join other streams that flow into the Wadi's central and down-stream areas. This runoff replenishes the shallow alluvium deposits and aquifers. Wadi Fatimah is able to partially compensate for the impact of its groundwater extraction with a recharge rate of +0.22±0.22 mm/yr. The integrated method used in this study is a helpful and economical way to evaluate groundwater resource variability over Wadi Fatimah region and its surrounding province.